Application of Competition Law Against Business Communities Using Disruptive Innovation - Maryanto Maryanto; Lathifah Hanim (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2019)
In this globalization era, competition among businesses in the relevant market is very tight. The businesses still struggle to compete with business competitors in the relevant market. The formulation of the problem show the application of Competition Law Against The Business Communities Using Disruptive Innovation. The method used is doctrinal and non-doctrinal. The data used are primary data is data obtained directly from the source and the respondents and secondary data is data obtained from the literature. Analysis of the data used is the qualitative analysis.Research results are. Application of competition law to businesses that use disruptive innovation is disruptive innovation has a major impact on competition in the market concerned, namely the consumers, consumers can be prosperious, and against the competition, then the conventional business operators must improve in order to compete. The first step that must be carried out by the Commission in analyzing whether the behavior of taxi online or not anti-competitive conduct in the market concerned, the Commission specifically define the relevant market definition in advance. Even when the market changed or created by a disruptive innovator, competition authorities (Commission) faced with the need for the existing market segmentation or determining a new market. Determination of the relevant market is very important to analyze whether a taxi online anti-competitive conduct and whether it has market power and dominant position which may misuse. Model law relationship triangle in the transport line between online app provider producers and consumers should be clarified first. Limitation of liability as a legal subject of legal entities in the transportation business online application the extent of the responsibility. Under the laws relating to the legal entity must sphere of responsibility of legal entities is regulated and contained in the constitution of the legal entity itself. The scope and responsibilities of legal entities governed the rights and obligations of legal entities in the statutes and households (AD / ART entity). The online system of transportation is honest and does not impede competition there is no dominant position in the online business of transportation in producing and market share as qualification monopolistic practices and unfair business competition. Other online transport entrepreneurs to enter the market is not hampered transport other online who want to enter the transportation market online. Evidently many online businesses transport both two (2)-wheel or four (4)-wheel rampant in many cities.Keywords: Competition, Business Communities, Disruptive Innovation.